2019
DOI: 10.1155/2019/3176018
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Kelulut Honey on Fasting Blood Glucose and Metabolic Parameters in Patients with Impaired Fasting Glucose

Abstract: Background. Impaired fasting glucose (IFG) poses a higher risk of diabetes. Honey has been reported to improve metabolic abnormalities including lowering hyperglycemia. This study is sought at determining the effect of Malaysian Kelulut honey (KH) on fasting glucose levels and metabolic parameters in IFG patients. Methods. This quasi-experimental intervention study of 30-day duration was conducted among 60 adult patients with IFG. They were allocated into taking 30 g/day KH group (experimental group, n=30) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 34 publications
(36 reference statements)
3
15
1
Order By: Relevance
“…[ 112 ]. Recent findings by Rashid et al (2019) supported a prior claim that the ingestion of Kelulut honey daily for 30 days has no significant effect on fasting glucose and fasting lipid profile in patients with impaired fasting blood glucose [ 109 ]. The authors suggested short-duration ingestion of Kelulut honey as the factor for the insignificant result.…”
Section: Medicinal Properties Of Tualang Gelam and Kelulut Honeysmentioning
confidence: 83%
See 1 more Smart Citation
“…[ 112 ]. Recent findings by Rashid et al (2019) supported a prior claim that the ingestion of Kelulut honey daily for 30 days has no significant effect on fasting glucose and fasting lipid profile in patients with impaired fasting blood glucose [ 109 ]. The authors suggested short-duration ingestion of Kelulut honey as the factor for the insignificant result.…”
Section: Medicinal Properties Of Tualang Gelam and Kelulut Honeysmentioning
confidence: 83%
“…Only Tualang and Kelulut honeys were found to have an anti-diabetic effect in three animal studies [ 50 , 107 , 108 ] and two human studies [ 109 , 110 ], as summarised in Table 7 . Studies using a diabetic model of rat showed that Tualang honey possessed moderate hypoglycaemic effect [ 50 ], improved liver enzyme profile [ 107 ], and possessed a synergetic benefit on glycaemic and metabolic profiles when administered together with metformin or glibenclamide [ 108 ].…”
Section: Medicinal Properties Of Tualang Gelam and Kelulut Honeysmentioning
confidence: 99%
“…Nik Hussein et al also revealed that 20 g/day Tualang honey along with hormonal replacement therapy (HRT) compared to HRT alone did not have substantial effects on blood pressure, lipid profile, glucose level, BMI, and WC in postmenopausal women after 4 months [ 34 ]. Based on the report published by Rashid et al, 30 g/day Malaysian Kelulut honey did not change FBS, lipid profiles, blood pressure, and BMI in patients with IFG after 30 days as compared to control [ 35 ]. However, Bahrami et al demonstrated that natural honey reduced bodyweight, FBS, and LDL-C/HDL-C ratio in patients with T2DM after 8 weeks compared to controls, but no changes were observed in HbA1c and lipid profiles [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Notably, they adjusted findings for baseline values. Rashid et al showed that consumption of 30 g/day Kelulut honey did not affect the glycemic status, lipid profiles, blood pressure, and BMI compared to those without taking honey after 1 month in patients with impaired fasting glucose [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, honey has been shown to scavenge reactive oxygen species (11) . Increased reactive oxygen species caused by metabolism of excessive glucose and/or NEFA has been identified as a contributor to β-cell dysfunction (12) . Therefore, we hypothesised that dietary honey intake may lower the onset of prediabetes.…”
mentioning
confidence: 99%